A Semiotic Analysis of Multicultural Values in an English Textbook for a Primary School - Zulfa, Siti; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research aims to discover multicultural values using semiotic analysis in an English textbook. This research is qualitative methodology. The sample of this research is an English textbook under the title ''Big English 5'' used in a private primary school in Indonesia. The data were gathered by documentation of the signs in texts and pictures in that English textbook and were analyzed by using semiotic analysis used Barthes's theory (1977) by integrating various theories to get the multicultural values represented in the English textbook. The findings showed that the texts and pictures represent each multicultural value covered in Big English 5. In addition, the most frequent multicultural value was found about Appreciate Other People's Cultural Products (AOPCP) with eleven items. The other most frequent multicultural value was found about International Cultural (IC) with eleven items. The multicultural values represent in the English textbook in pictures and texts consist of the things, places, foods, and traditions. Unfortunately, the Source Culture (SC) related to Indonesian culture was found merely two items, even though young learners use that English book at a primary school in Indonesia. In conclusion, the English textbook of Big English 5 contained multicultural values which could support young learners' English language process. However, this English textbook needs to add the content of Indonesian culture as the user of that English textbook. Hence, it could acquaint the Indonesian culture through English learning for young learners earlier. Besides, the role of English teachers and students becomes necessary to utilize the English textbook appropriately by designing activities that entangle multicultural values and the use of the English language during the learning process.